Love and death in Kubrick a critical study of the films from Lolita through Eyes wide shut - Webster, Patrick, 1953- (McFarland & Company, Inc., Publishers, 2010)
"This text explores the auteur's legacy, specifically positioning his body of work within the context of cultural theory. A single chapter is devoted to each of Kubrick's seven films. Attention is paid to the role of love and death in Kubrick's films, emphasizing his innovative exploration of love and sex, and the portrayal of mortality via masculine violence"--Provided by publisher.